Voices of Europe and Central Asia : New Insights on Shared Prosperity and Jobs - Dávalos, María E; Demarchi, Giorgia; Santos, Indhira; Kits, Barbara; Oral, Isil (World Bank, Washington, DC, 2016)
Does the data we traditionally use on poverty, inequality and labor markets capture the full picture? Qualitative evidence from 9 countries in Europe and Central Asia shows that people’s perceptions are not always well aligned with quantitative indicators. Increased polarization and the role of factors beyond people’s control, such as connections and social norms, are at the heart of this disconnect. This report discusses the implications of these findings for policy makers and the development community as we seek to better understand barriers to accessing jobs, reducing poverty and sharing prosperity.